2009
DOI: 10.1007/s10661-008-0719-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and analysis of noise levels in Ilorin metropolis, Nigeria

Abstract: Evaluation and analysis of noise pollution levels have been carried out to determine the level of noise and its sources in Ilorin metropolis. Noise measurements have been done in the morning, at noon, in the evening, and at night to determine noise pollution all over the city. The selected areas of study are commercial centers, road junctions/busy roads, passenger loading parks, and high-density and low-density residential areas. The road junctions had the highest noise pollution levels, followed by commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 15 publications
4
25
0
1
Order By: Relevance
“…This is very dangerous to the health of the people in these areas. According to World Health Organization, noise level of 60 dB(A) can result in temporary hearing impairment and 100 dB(A) can cause permanent impairment [11] for a certain period of exposure time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is very dangerous to the health of the people in these areas. According to World Health Organization, noise level of 60 dB(A) can result in temporary hearing impairment and 100 dB(A) can cause permanent impairment [11] for a certain period of exposure time.…”
Section: Resultsmentioning
confidence: 99%
“…The noise pollution was lowest compared to Klang Valley during daytime and night time because majority of the residents are away from their home in the afternoon. Some are in their offices, markets, or shops while children were in their schools by this time of the day [11]. Therefore, no trip generated by the residents during afternoon.…”
Section: Resultsmentioning
confidence: 99%
“…Noise levels at Parking Plant-recycling Unit, Parking Plant-Roto Parker Unit, Cement mill, and Raw-mill all exceeded the standard. Oyedepo and Saadu [54] reported that only 17% of the measurements in the parking, clay crusher and red soil silo had acceptable noise levels below 80 dB, while 83% of measurements for those sections had noise levels between 80-90 dB. About 50% of measurements at the limestone crusher had noise levels between 80-90 dB, with 50% were above 90dB.…”
Section: ) Air Quality Parameters In Dangote Cement Factory Ibesementioning
confidence: 99%
“…Noise survey in various R. Vijay et al cities throughout the world has revealed that traffic noise is the largest contributor to recorded sound levels and the most important source of annoyance [3][4][5][6][7]. Traffic is a significant part of urban environment contributing to about 55% of total urban noise [8,9].…”
Section: Introductionmentioning
confidence: 99%